(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
The study included two groups, it has been designed as two experiments , in the first experiment,24 rats have divided into four subgroups , the first subgroup received the distal water which considering the control group and the other three subgroups have given a different aluminum chloride concentrations (80, 160, 240 mg/kg/day) for 45 days . In the second experiment 24 rats divided into four subgroups ,the first one received a 1 ml/kg concentration of Nigella Sativa oil, which considered as a negative control group while the rest of the subgroups received the same previous concentrations of aluminum chloride in addition to 1ml/ kg concentrations of Nigella sativa oil . The study showed a significant reduction(p<0.05) in the thyroid gland hormones level ( T3) in the (160 mg/kg) concentration and T4level at (240,160 mg/kg) with a significant elevation(p<0.05) in TSH in the same concentration when compared with positive control. The treatment with Nigella sativa oil enhance the levels of T3 in the 240 mg/kg. For the histological changes of the studied organs , these changes represented by a degeneration of epithelial cells that surrounded the thyroid gland follicle , infiltration of inflammatory cells in the lumen of the follicle, then when compared with groups treated by oil of Nigella sativa, there is a little improvement in some of the tissues which represented by a vacaules in thyroid follicles which it refers to the activity of the gland regeneration of epithelial cells that surrounding the follicle , there’s appositive effects of oil of Nigella sativ on the level of T3 and the histology of thyroid gland changes which caused by the toxicity of 240 mg/kg of aluminum chloride .